2009
DOI: 10.1111/j.1442-200x.2008.02783.x
|View full text |Cite
|
Sign up to set email alerts
|

Japanese clinical guidelines for juvenile orthostatic dysregulation version 1

Abstract: This clinical practice guideline provides recommendations for the assessment, diagnosis and treatment of school-aged children and juveniles with orthostatic dysregulation (OD), usually named orthostatic intolerance in USA and Europe. This guideline is intended for use by primary care clinicians working in primary care settings. The guideline contains the following recommendations for diagnosis of OD: (i) initial evaluation composed of including and excluding criteria, the assessment of no evidence of other dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
76
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 71 publications
(82 citation statements)
references
References 49 publications
(70 reference statements)
3
76
0
3
Order By: Relevance
“…We applied the Schellong test, i.e., the active stand ing test for the adult patients (≥ 20 years), and the new ortho static test (described below), for the adolescent patients (< 20 years). 7 We evaluated the state of sleep phase during the inves tigation using the severity level criteria for delayed sleep phase syndrome (DSPS) devised by Ohta et al 13 We also confirmed the use of medications (vitamin B 12 , GABAergic agents [such as benzodiazepines and nonbenzodiazepine hypnotics], and ramelteon). We performed the OD test when the patient came for a routine medical examination.…”
Section: Methodsmentioning
confidence: 98%
See 4 more Smart Citations
“…We applied the Schellong test, i.e., the active stand ing test for the adult patients (≥ 20 years), and the new ortho static test (described below), for the adolescent patients (< 20 years). 7 We evaluated the state of sleep phase during the inves tigation using the severity level criteria for delayed sleep phase syndrome (DSPS) devised by Ohta et al 13 We also confirmed the use of medications (vitamin B 12 , GABAergic agents [such as benzodiazepines and nonbenzodiazepine hypnotics], and ramelteon). We performed the OD test when the patient came for a routine medical examination.…”
Section: Methodsmentioning
confidence: 98%
“…The protocol for the new orthostatic test established by Tanaka et al 6,7 for use in adolescents was as follows: (1) Rest for 10 min in the supine position. Put a manometer cuff on the arm.…”
Section: Test Protocol For Odmentioning
confidence: 99%
See 3 more Smart Citations